The Chinese perception of quality: model building and analysis based on consumers' perception - Hong Cheng; Dandan Li; Lianfa Luo (Journal of Chinese Management, 2014)
Theory construction and data reconstruction are required for the evaluation of quality in China. Taking into consideration existing mature quality evaluation models (particularly the methods of evaluating customer satisfaction) and China's unique national conditions during its economic transition, four dimensions are proposed to evaluate quality in China: consumer satisfaction with quality, product safety, government regulations on quality, and citizen's concept of quality. Based on empirical investigation data in this framework, the overall evaluation of quality in China is summarized as quality in China has just reached a general standard, product safety remains steady as a whole, government quality regulations are ineffective, and Chinese citizens' concept of quality is poor. Correlation analyses show a positive relation between the effectiveness of government regulation on quality and Chinese citizens' concept of quality, consumer satisfaction with quality, and product safety. Finally, the paper proposes the implementation of an emphasis on product safety during quality elevation and quality improvement systems, such as the constant enhancement of quality regulation effects and Chinese citizens' concept of quality, to drive quality development.
Keywords: 650; Quality evaluation; Model building; Product safety; Consumers' perception; Survey method